Re-Imagining Higher Education: Time, Learning, and Risk - Collins-Nelsen, Rebecca; Hill, Michaela; Maclachlan, John C. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
This article recommends institutional changes to higher education related to time, learning, and risk that would better serve the contemporary student population and increase opportunities for life-long and interdisciplinary learning. To begin, the changing demographic of university students will be outlined, along with suggestions about how traditional institutional arrangements are no longer conducive to optimal learning environments. Next, a review of the history of the academic year will be provided, that will show a snapshot of post-secondary academic calendars in Canada. Relatedly, a discussion of the potential drawbacks and benefits to accelerated courses will be deliberated, as well as the role of risk in terms of how this shapes students’ course selection. Finally, an example of a pilot program at McMaster University, a large research-intensive university in Ontario, Canada, which is specifically designed to account for the pitfalls outlined above, will be discussed. Taken together, it will be argued that having full-course offerings on a year-round basis, providing various options for course lengths, and adjusting evaluations to reduce students’ conceptions of ‘risk’ will better adapt institutes of higher education for the twenty-first century.